Emergency Peripartum Hysterectomy in a Tertiary Care Centre and Medical College Of Ranchi, Jharkhand, India : A Retrospective Study (Global Journal of Medical Research, 2019)
Abstract not found
Keywords: emergency peripartum hysterectomy; atonic pph; rupture uterus; placenta praevia; placenta accreta